Reply to: Comment on: Revascularization in Patients Aged 80 Years and Older with Acute Myocardial Infarction. Issue 1 (12th November 2020) - Phan, Derek Q.; Zadegan, Ray; Lee, Ming‐Sum
Abstract : This letter comments on the letter by Alain Putot